Duální kariéra ve sportu a nutnost její institucionalizace v Ceské republice - Nová, J. (Telesna Kultura, 2016)
The paper on the base of a content analysis of European documents and manuals in the field of dual career in the sport deals with the evaluation of their implementation in the context of the Czech Republic. The analysis is complemented by own investigation among elite athletes and their coaches using the online questionnaire. Conclusions form the qualitative analysis are then used to formulate proposals to support training and subsequent transition of elite athletes to the labour market using the theory of institutionalization.